Autism: a curse on today’s society - Sarkar, Snehashis; Choudhury, Ananta; Saha, Suman; Dey, Biplab Kumar (Creative Pharma Assent, 2020)
Autism is a group of neurodevelopment disorders characterized by impaired communication, impaired social interaction and restricted, repetitive and stereotyped patterns of behaviours or interests in the first 3 years of life. It shows a strong male bias and found four times more in males than in females. According to a study in the US, in 2014, overall 1.68% of victims were reported to have Autism Spectrum Disorder (ASD), whereas the percentage was increased by 15% and 150% respectively over the year 2012 and 2000. Numerous genes have been discovered that have roles in ASD but still a good understanding of the pathophysiological process of ASD is not established. ASD costs are estimated to be approximately 250 billion annually in the U.S. Moreover, it is suggested that by 2025, ASD costs will rise to over 450 billion. Thus, the financial burden on families is increasing. There is no effective screening tool for proper diagnosis is available. Based on Infant Toddler Checklist (ITC) and Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM-5) some tests like ADOS-G, ADI-R, CARS etc. are used for diagnosis. There are medications to cure symptoms but no single medication for ASD. However, some therapies (like ABA- Applied Behavioural Analysis, DTT- Discrete Trial Training, and Symptomatic treatments, etc.) are there that show positive responses towards improvement from a disease state. Some crucial advancement has been achieved in the last decades. Here in the work we have focused on the diagnostic methods and treatment available for the symptoms of Autism. So, it can be said that the day is not too far away when the remedy to cut the curse of autism will be in our hands.